Democracia aprisionada: o controle da liberdade de navegação na internet e os riscos à justiça global - Polli, Fernando Gabbi (2020)
Contemporary society has incorporated the use of information technologies in its daily life, organizing itself in a network. This engineering has a global reach, since all individuals are interconnected politically, socially and economically, and from this reality, new issues arise that must be legally protected. Among these emerging rights are those inherent in the use of the world wide computer network, a space in which users seek to establish relationships, whether personal, business and / or informational. This new reality has strong social, political and legal impacts, specifically those arising from the use of data from network users to direct their navigation. Thus, based on this reality, the following questions arise: Does the direction of navigation on the world wide web, based on user data collection, undermine human rights freedom of navigation and, consequently, free information and self-determination? And what are the consequences of this direction for contemporary democracies? Thus, the present dissertation aims to analyze the virtual environment in order to verify if and how the limitation of individual freedom affects fair and democratic social organization. From the perspective of egalitarian liberalism, the present research seeks in the precepts of global justice the categories to analyze such phenomenon. To develop the present work, the deductive approach method was developed, developed on a dialectical reasoning. Initially, the moral and legal foundations that allow us to affirm that free internet browsing are an emerging right required for global justice and fundamental for the development of democracy were verified. In a second moment, the architecture of the worldwide computer network was studied through the identification of the actors inserted in this environment, their interests and practices that collaborate with the conditioning of the virtual experience of the user, which makes the internet an unequal environment regarding the distribution of information. freedoms. Finally, case studies of the US presidential elections in 2016 and Brazil in 2018 were conducted, which showed that the internet is an injustice instrument, where the individual user's freedom is limited in such a way as to reflect on public freedoms, especially in the direct exercise of democracy, suffrage.